Hydromorphological Modeling of Vertical Grain Sorting Process. Insights from the Günter Experiment 6 using TELEMAC & SISYPHE. (London Journal of Engineering Research, 2024)
.
Keywords: TELEMAC; SISYPHE; bed roughness; Shield coefficient; bed load transport formulae; Gain Size; hydromorphological modeling; sediment transport; numerical simulation; river engineering